A new stonefly species Neoperla lamesae sp. nov. (Plecoptera: Perlidae) from Quezon City, Philippines, with associated life stages and notes on Neoperla recta Banks, 1913 taxonomy - Ricafort, Jondemarco A.; Pelingen, Arthien Lovell; Fontanilla, Ian Kendrich C.; Bae, Yeon Jae; Uy-Yabut, Christine Jewel C. (Zootaxa, 2026)
A new Plecoptera species Neoperla lamesae sp. nov. Ricafort & Uy-Yabut, 2025 is described and figured from La Mesa Watershed Reservation, Quezon City, Philippines. The description includes all the life stages from egg to adult, confirmed to be from the same species using DNA barcoding. The male adult penis closely resembles a locality morphotype of N. recta. The associated female adult is differentially diagnosed against the N. recta female lectotype by the vaginal sclerites and the polygonal chorion pattern of the egg. The COI data suggest species divergence of two N. recta male penis morphotypes, the Makiling and Imugin morphotypes. The observed COI divergence and previously documented penis variability of N. recta suggest a reevaluation of the species complex.